N—H...O and N—H...N interactions in three pyran derivatives. (9th May 2013) - Vishnupriya, R.; Suresh, J.; Sivakumar, S.; Kumar, R. Ranjith
<x xml:space="preserve">Abstract</x> The three pyran structures 6‐methylamino‐5‐nitro‐2, 4‐diphenyl‐4H‐pyran‐3‐carbonitrile, C19H15N3O3, (I), 4‐(3‐fluorophenyl)‐6‐methylamino‐5‐nitro‐2‐phenyl‐4H‐pyran‐3‐carbonitrile, C19H14FN3O3, (II), and 4‐(4‐chlorophenyl)‐6‐methylamino‐5‐nitro‐2‐phenyl‐4H‐pyran‐3‐carbonitrile, C19H14ClN3O3, (III), differ in the nature of the aryl group at the 4‐position. The heterocyclic ring in all three structures adopts a flattened boat conformation. The dihedral angle between the pseudo‐axial phenyl substituent and the flat part of the pyran ring is 89.97 (1)° in (I), 80.11 (1)° in (II) and 87.77 (1)° in (III). In all three crystal structures, a strong intramolecular N—H...O hydrogen bond links the flat conjugated H—N—C=C—N—O fragment into a six‐membered ring. In (II), molecules are linked into dimeric aggregates by N—H... O(nitro) hydrogen bonds, generating an R22(12) graph‐set motif. In (III), intermolecular N—H...N and C—H...N hydrogen bonds link the molecules into a linear chain pattern generating C(8) and C(9) graph‐set motifs, respectively.